HUBUNGAN PENGETAHUAN DAN PERILAKU SISWA TENTANG BULLYING TERHADAP KESEHATAN MENTAL SISWA KELAS XII IPA 1 DI SMA NEGERI 1 DOLOKSANGGUL TAHUN 2024 - Lumbantoruan, Benny Maria; Sihombing, Rico PC; Manalu, Joys Ganda Asih Manalu; Silaban, Lusianna (Jurnal STIKes Kesehatan Baru, 2024)
Bullying is a deliberate act or aggressive behavior, committed by a group of people or a person repeatedly and over time to a victim who is unable to defend himself easily or as a systematic abuse of power/power. Where low knowledge and poor behavior can have a big impact on a student's mental health. The purpose of the study: this is to find out "The Relationship of Knowledge and Student Behavior About Bullying to the Mental Health of Grade XII Science 1 Students at SMA Negeri 1 Doloksanggul, Humbang Hasundutan Regency in 2024". Type of research: descriptive quantitative analysis using a crosssectional method where independent and dependent variables are studied simultaneously. This research was conducted from March-May 2024 with a population of 43 people. Sampling was done using a total sampling with a total of 43 respondents. Data collection using questionnaires is then examined and processed. From the results of the chi-square chi-square test calculated with the Chi-square table, where it is known that X2 counts (4.968) > X2 Table (1.683) with df = 1 (? = 0.05), then there is a relationship. There is a Relationship between Student Behavior Regarding Bullying to the Mental Health of Grade XII Science 1 Students at SMA Negeri 1 Doloksanggul, Humbang Hasundutan Regency in 2024. From the results of the chi-square chi-square test calculated with the Chi-square table, where it is known that X2 counts (7,947) > X2 Table (1,683) with df = 1 (? = 0.05). So the conclusion in the study is that there is a Relationship between Student Knowledge About Bullying and Mental Health of Class XII Science 1 students at SMA Negeri 1 Doloksanggul, Humbang Hasundutan Regency in 2024. Based on the results of the study, it is hoped that respondents will read or seek a lot of information about what bullying is and its prevention, as well as cooperate with health workers, especially about preventing bullying behavior.